Problematika Pendaftaran Tanah Bagi Ahli Waris Keturunan Tionghoa Yang Perkawinan Orang Tuanya Tidak Tercatat - Rismawaty Rismawaty; Dedi Harianto; T. Keizerina Devi Azwar; Faisal Akbar (Iuris Studia: Jurnal Kajian Hukum, 2021)
Registration of property rights is part of land registration. Article 19 paragraph (1) of the LoGA stipulates that